2017
DOI: 10.2302/kjm.2017-0002-ir
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Hypoxia Response in Retinal Development and Pathophysiology

Abstract: The hypoxia response is a fundamental phenomenon mainly regulated by hypoxia-inducible factors (HIFs). For more than a decade, we have investigated and revealed the roles of the hypoxia response in the development, physiology, and pathophysiology of the retina by generating and utilizing cell-typespecific conditional knockout mice. To investigate the functions of genes related to the hypoxia response in cells composing the retina, we generated various mouse lines that lack HIFs and/or related genes specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…A study reported that fenofibrate prevents pathological neovascularization in the rat OIR model by suppressing HIF and VEGF [26]. HIF plays an important role in maintaining tissue homeostasis after exposure to hypoxic conditions and other stress stimuli [27,28]. Thus, we also focused on the HIF/VEGF system as a potential pathway activated by pemafibrate.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that fenofibrate prevents pathological neovascularization in the rat OIR model by suppressing HIF and VEGF [26]. HIF plays an important role in maintaining tissue homeostasis after exposure to hypoxic conditions and other stress stimuli [27,28]. Thus, we also focused on the HIF/VEGF system as a potential pathway activated by pemafibrate.…”
Section: Discussionmentioning
confidence: 99%
“…Among the oxygen sensing transcription factors hypoxia-inducible factor 1 (HIF-1) is a heterodimer composed of two subunits: a labile HIF-1α subunit and a stable HIF-1β subunit. Under normoxia, HIF-1α is continuously degraded by proteasome, but when oxygen becomes limiting, HIF-1α escapes degradation, accumulates in the cell, is imported into the nucleus, dimerizes with HIF-1β and activates dozen of genes encoding for a multitude of pro-angiogenic and inflammatory factors that are involved in both excessive vasopermeability and neovessel growth [84]. HIF-1 also activates the expression of genes related to ECM degradation (for Ref., see [85]) and modulates the expression of genes involved in autophagy, apoptosis, redox homeostasis and immunity [86], thus suggesting a role as a multiplicative factor in mediating an abundance of pathological responses to an ischemic insult.…”
Section: Mechanisms Of Upar Signalingmentioning
confidence: 99%
“…3 Under ocular ischemia or other cellular stress conditions in the retina, retinal HIF can be stabilized, and it induces a pivotal shift in hypoxic retinal cells to undergo neovascularization and/or pathological anaerobic metabolic processes. 5,6 It was reported that focal HIF-1α expression increased with acute retinal ischemia in humans, 7 and an increase in HIF-1α protein expression was also observed in the chronically progressed glaucomatous retina and the optic nerve head. 8 Moreover, HIF inhibition has been suggested to be therapeutic in various experimental ocular diseases including age-related macular degeneration, retinopathy of prematurity, diabetic retinopathy, glaucoma and corneal injuries.…”
Section: Introductionmentioning
confidence: 99%